2016
DOI: 10.1037/tep0000115
|View full text |Cite
|
Sign up to set email alerts
|

Who matters most? The contribution of faculty, student-peers, and outside support in predicting graduate student satisfaction.

Abstract: Social support is one variable that has been linked to a number of positive academic and personal outcomes for graduate students. However, little is known about which sources of social support (faculty mentors, student-peers, family/friends outside of the program) best predict graduate student satisfaction with their training program. The following study examined the relationship between social support from 3 sources (peers, family/friends, and faculty) and 2 indices of satisfaction (program and general life) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 21 publications
4
74
1
Order By: Relevance
“…Findings suggest that this mutual engagement with TD fostered a sense of collaborative discovery by faculty and students, thus enhancing students' experience of support. This type of co-learning is of interest because perceived faculty support is related to student program satisfaction, as well as student life satisfaction (Tompkins et al, 2016). While the TD students perceived a high level of support from faculty, students in traditional programs perceived lower levels of socioemotional support from faculty than from family, friends, and student-peers (Tompkins et al, 2016).…”
Section: Faculty Benefits and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings suggest that this mutual engagement with TD fostered a sense of collaborative discovery by faculty and students, thus enhancing students' experience of support. This type of co-learning is of interest because perceived faculty support is related to student program satisfaction, as well as student life satisfaction (Tompkins et al, 2016). While the TD students perceived a high level of support from faculty, students in traditional programs perceived lower levels of socioemotional support from faculty than from family, friends, and student-peers (Tompkins et al, 2016).…”
Section: Faculty Benefits and Barriersmentioning
confidence: 99%
“…This type of co-learning is of interest because perceived faculty support is related to student program satisfaction, as well as student life satisfaction (Tompkins et al, 2016). While the TD students perceived a high level of support from faculty, students in traditional programs perceived lower levels of socioemotional support from faculty than from family, friends, and student-peers (Tompkins et al, 2016). Graduate school is a notoriously stressful endeavor and high stress can interfere with academic performance and degree completion (Lovitts, 2001).…”
Section: Faculty Benefits and Barriersmentioning
confidence: 99%
“…For a group of students who may be more susceptible to stressors, it is important to consider possible sources of strain and support, such as faculty members. I argue that faculty may significantly affect graduate student parents' experiences of role enhancement and role conflict because the literature suggests that faculty have a strong influence on student lives (Tompkins, Brecht, Tucker, Neander, & Swift, 2016). Prior research has focused only on advisors (Barbuto, Story, Fritz, & Schinstock, 2011;Komarraju, Musulkin, & Bhattacharya, 2010;Rice et al, 2009;Schlosser & Gelso, 2001Schlosser & Kahn, 2007Schlosser, Knox, Moskovitz, & Hill, 2003), but I hypothesize that because of their positions as instructors and committee members, other faculty members may impact graduate student parents, as well.…”
Section: Contextmentioning
confidence: 97%
“…According to recent research, faculty support more strongly predicted graduate students' satisfaction with their program and with life in general than did support from family, friends, or student peers (Tompkins et al, 2016). Research also suggested that faculty members affect college students' attitudes toward research (Schlosser & Gelso, 2001), motivation (Komarraju et al, 2010), effort (Barbuto et al, 2011), and overall satisfaction with life (Tompkins et al, 2016).…”
Section: Contextmentioning
confidence: 99%
See 1 more Smart Citation